Effect of prone posture in the management of non-intubated patients with acute respiratory failure caused by SARS-CoV-2: retrospective study - Escorcio, Renata; Andrade, Luiza Barreto; Guedes, Emília Brollo; Mendes, Luciane Frizo (Revista da Faculdade de Ciências Médicas de Sorocaba, 2023)
The SARS-CoV-2 pandemic, more known as COVID-19, has brought some big challenges to the multiprofessional team regarding these patients. Having the potential to aggravate, this desease can acute respiratory distress syndrome (ARDS). Some conditions that may influence the risk of severity of the disease are advanced age, comorbidities and male sex. Studies reported that the prone position is used to treat hypoxemic acute respiratory failure in non-intubated patients with COVID-19, acting through gas exchange. Studies show the need to identificate subpopulations of patients with ARDS due to COVID-19 that may benefit from the active prone position. Objective: the aim of this study was to verify the effects of the active prone position and its relation with gender, comorbidities, age, pulmonary impairment, APACHE score and length of stay in the ICU. Method: This is a retrospective cross sectional observational study, performed through analysis of medical records. The patients were classified according to wether or not they performed the active prone position during the ICU stay. Result: There is a significant difference between the gender frequency distribution in the two groups (p=0.019). The group that performed the active prone position was mostly composed by patients of the male gender (70%). There is a significant difference between the APACHE scores in the two groups (p=0.03). There is a significant difference between the length of stay in the ICU between the groups (p=0.04). No patient was intubated or died. Conclusion: The active prone position can be a safe and feasible procedure.